The role of captive power plants in the Bangladesh electricity sector - Sakib-Bin-Amin; Tooraj Jamasb; Manuel Llorca; Laura Marsiliani; Thomas I. Renström (Asian Development Bank Institute (ADBI), 2021)
Captive power plants (CPPs) in many emerging and developing countries play a significant role in the electricity sector. This is mainly due to unreliable electricity supplies from state-owned utilities and challenges in accessing the national grid, especially in remote and rural areas. Integrating the captive capacity with the on-grid supply can improve resource utilization in the electricity market. In this study, we focus on the role of CPPs in Bangladesh. We start by providing recent stylized facts and survey the experience of other countries. We then use a dynamic stochastic general equilibrium (DSGE) model to examine the effects of allowing CPPs to sell their excess output to the national grid at regulated prices. We find that opening the grid to CPPs would reduce the industrial output and GDP due to pre-existing energy price distortions. We also show that the Bangladesh economy would become more vulnerable to oil price shocks if CPPs were connected to the national grid. We conclude that the government should not open the grid to CPPs yet. Instead, it should first consider alternative reforms, such as taking steps to reduce the price distortions and enabling a competitive market environment.
Keywords: D58; L94; Q43; Q48; 330; Bangladesh; captive power plants (CPPs); DSGE model; electricity generation; second-best theory